2015
DOI: 10.3389/fgene.2015.00125
|View full text |Cite
|
Sign up to set email alerts
|

Non coding RNAs in aortic aneurysmal disease

Abstract: An aneurysm is a local dilatation of a vessel wall which is >50% its original diameter. Within the spectrum of cardiovascular diseases, aortic aneurysms are among the most challenging to treat. Most patients present acutely after aneurysm rupture or dissection from a previous asymptomatic condition and are managed by open surgical or endovascular repair. In addition, patients may harbor concurrent disease contraindicating surgical intervention. Collectively, these factors have driven the search for alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 71 publications
0
33
0
2
Order By: Relevance
“…Second, insufficient funding is an important barrier to performing basic research, and many clinicians believe that they do not have enough time to perform basic science research along with patient care [17]. Much more basic research is needed to elucidate the mechanism of AD to allow better clinical treatment strategies, as several of the articles (Duggirala A et al [18], Stankowski RV et al [19] and Milewicz DM et al [20]) in our T100 list, although published in journals with a relatively low IF provide important data about AD.…”
Section: Discussionmentioning
confidence: 99%
“…Second, insufficient funding is an important barrier to performing basic research, and many clinicians believe that they do not have enough time to perform basic science research along with patient care [17]. Much more basic research is needed to elucidate the mechanism of AD to allow better clinical treatment strategies, as several of the articles (Duggirala A et al [18], Stankowski RV et al [19] and Milewicz DM et al [20]) in our T100 list, although published in journals with a relatively low IF provide important data about AD.…”
Section: Discussionmentioning
confidence: 99%
“…VSMCs are the major resident cells in the aortic wall, and they can maintain aortic architecture by matrix synthesis . miRNAs have been demonstrated to be involved in the development of aortic aneurysm by regulating VSMCs proliferation, differentiation, apoptosis, migration, or ECM . To investigate the role of miR‐195 in AAA formation, we detected the effect of miR‐195 on VSMCs proliferation and apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…25 migration, or ECM. 26 To investigate the role of miR-195 in AAA formation, we detected the effect of miR-195 on VSMCs proliferation and apoptosis in vitro. As might be expected, we found that miR-195 overexpression suppressed proliferation and promoted apoptosis of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar abnormalities can be identified by measuring alpha II-spectrin breakdown products in the serum [33].Non-coding RNA (ncRNAs) is emerging as new fundamental regulators of gene expression (Table 2). microRNAs and lncRNAs work as clinical biomarkers for aortic aneurysm [7].…”
Section: Genetic Markersmentioning
confidence: 99%
“…An aneurysm is a local dilatation of a vessel wall which is >50% of its original diameter. Aortic aneurysms are among the most challenging to treat [7]. Similarly, early stage heart failure in adults is a severe congenital heart disease remains elusive in diagnosis (Table 1).…”
Section: Introductionmentioning
confidence: 99%